ZigBee based wireless energy monitoring system (WEMS) - Koh, Chun Kiat. (2012)
In the current market place for power engineering products, there are many proprietary energy wireless monitoring systems with standalone monitoring functionalities being integrated into them, sometimes at a high cost. As a result, attempts to integrate different products from different manufacturers proved to be difficult. This thesis aims to resolve this issue by designing and implementing a Wireless Energy Monitoring System (WEMS) framework for adoption by electrical power engineering applications. In addition, it should also be highly customizable and interface-able, so that other non-power engineering applications can also utilize the framework, making it a truly versatile solution in different fields. This project will attempt to use the latest Jennic ZigBee Pro Wireless Communication Technology, develop the backend server data logging application, frontend web interface and use open-source software in order to create a simple, low-cost and easily deployable wireless monitoring system for general commercial and non-commercial use, such as for research teams in the universities.